A microsporidian pathogen of the predatory beetle Rhizophagus grandis (Coleoptera: Rhizophagidae) - Yaman, Mustafa; Radek, Renate; Weiser, Jaroslav; Aydin, Cicek (Folia parasitologica, 2010)
A new Microsporidium sp. infects Rhizophagus grandis Gyllenhall, a beetle which preys on the bark beetle Dendroctonus micans Kugellan in Turkey. Mature spores are single, uninucleate, oval in shape (3.75 +/- 0.27 microm in length by 2.47 +/- 0.13 microm in width), with a subapically fixed polar filament. The polar filament is anisofilar, coiled in 7-8 normal and 3-4 reduced coils. Other characteristic features of the microsporidium are the four/five nuclear divisions to form 16/32 (commonly 16) spores, subpersistent sporophorous vesicles (pansporoblasts) remaining till formation of the endospore, and the vesicles dissolved with free mature spores. The polaroplast is divided into three zones: an amorphous zone, dense layers, and a lamellartubular area extending to the central part of the spore.
Keywords: Microsporidia; Animals; zvířata; brouci; Coleoptera